2017
DOI: 10.1371/journal.pone.0171807
|View full text |Cite
|
Sign up to set email alerts
|

Advancing the match-mismatch framework for large herbivores in the Arctic: Evaluating the evidence for a trophic mismatch in caribou

Abstract: Climate-induced shifts in plant phenology may adversely affect animals that cannot or do not shift the timing of their reproductive cycle. The realized effect of potential trophic “mismatches” between a consumer and its food varies with the degree to which species rely on dietary income and stored capital. Large Arctic herbivores rely heavily on maternal capital to reproduce and give birth near the onset of the growing season but are they vulnerable to trophic mismatch? We evaluated the long-term changes in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
87
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(89 citation statements)
references
References 62 publications
0
87
2
Order By: Relevance
“…Although previous studies have contrasted satellite and plot-scale NDVI as estimators of arctic vegetation biomass [2], we are unaware of other work that explicitly contrasts the predictive power of NDVI metrics for properties of vegetation across multiple scales. Given the current evidence for rapid changes in physical and environmental phenologyin the Arctic, conflicting consequences of a phenology mismatch between migratory herbivores and their food resources [69,70], and an interest in forecasting the future of plant forage quality and quantity for herbivores [6], there is a compelling need to improve monitoring of forage plant quantity and quality at high latitudes. Appendix A Table A1.…”
Section: Resultsmentioning
confidence: 99%
“…Although previous studies have contrasted satellite and plot-scale NDVI as estimators of arctic vegetation biomass [2], we are unaware of other work that explicitly contrasts the predictive power of NDVI metrics for properties of vegetation across multiple scales. Given the current evidence for rapid changes in physical and environmental phenologyin the Arctic, conflicting consequences of a phenology mismatch between migratory herbivores and their food resources [69,70], and an interest in forecasting the future of plant forage quality and quantity for herbivores [6], there is a compelling need to improve monitoring of forage plant quantity and quality at high latitudes. Appendix A Table A1.…”
Section: Resultsmentioning
confidence: 99%
“…Studies from Tveraa et al (2013), Veiberg et al (2016), and Gustine et al (2017) found no evidence of a trophic mismatch between the onset of spring vegetation and Rangifer reproductive success in reindeer populations in northern Norway, Svalbard, or Alaskan caribou, respectively. In fact, it is characteristic of Arctic Rangifer populations to calve before spring green-up occurs.…”
Section: Summer Range Conditionsmentioning
confidence: 91%
“…Reliance on maternal body stores for foetal development rather than dietary income may mitigate negative effects of changing phenologies (Stephens et al 2009;Veiberg et al 2016;Gustine et al 2017). As previously noted, it has been well documented that many Rangifer populations calve before the onset of vegetation growth, reinforcing the importance of maternal capital for reproduction (Barboza and Parker 2008) and in some ways curtailing the conceptual potential for spring phenological mismatches.…”
Section: Summer Range Conditionsmentioning
confidence: 92%
See 2 more Smart Citations